The complete mitogenome dataset of the Critically Endangered estuarine pipefish, Syngnathus watermeyeri - Arsalan Emami-Khoyi (Data in Brief, 2024)
The Critically Endangered South African estuarine pipefish, Syngnathus watermeyeri, is one of the rarest teleost fish on the planet. In this analysed dataset, the complete mitochondrial genome of this species was assembled, annotated, and described. In addition, its evolutionary history was reconstructed in a Maximum Likelihood and a Bayesian framework. A circular mitochondrial contig 16 449 bp in length was assembled. A total of 13 protein-coding genes, 22 tRNAs and two rRNAs were annotated. The mitochondrial phylogenetic analysis showed that S. watermeyeri diverged from its widely distributed southern African sister species S. temminckii approximately 1.5 million years ago, and the ancestor of these two southern Afican pipefish species diverged from a clade of northern hemisphere pipefishes comprising S. acus, S. rostellatus, and S. typhle approximately 5.3 million years ago. The dataset presented here serves as the first step in understanding the evolutionary history of Africa's rarest pipefish.